THE ANTECEDENTS OF MSME PERFORMANCE: FROM CHARACTERISTICS OF ISLAMIC ENTREPRENEURS PERCEPTION - Fatmah Bagis; Mastur Mujib Ikhsani; Muhammad Muammar; Akhmad Darmawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The Theory of Planned Behavior (TPB) is one theory that has been widely applied in various fields of behavioral research, and several studies have proven that Islamic entrepreneurs must have characteristics. This study examines the antecedent of MSME performance from the point of view of the characteristics of Islamic entrepreneurs. This research was conducted in MSMEs in Purwokerto City on the grounds that there is still a lack of application of Islamic entrepreneurial characteristics in SME activities. The purpose of this study was to examine the effect of the characteristics of Islamic entrepreneurs (honesty, willpower, keeping promises, orderly administration, praying, paying zakat and alms, having leadership spirit) on the performance of MSMEs. The sample used was 87 Muslim MSMEs in Purwokerto. Primary data collection techniques are observation and discussion, direct observation in the field using a distributed questionnaire. The data analysis method used is Partial Least Square (PLS). The results showed that the unsupported hypothesis related to the variables of willingness to work hard, keep promises, Islamic leadership and pay zakat had no effect on the performance of Muslim SMEs in Purwokerto. Meanwhile, orderly administration, honesty and prayer support the performance of Muslim SMEs in Purwokerto, thus supporting the acceptance of the hypothesis.